Post-traumatic growth level in a sample of physically injured people in Damascus governorate according to sex, age, education variables (Journal of Hama University, 2023)
Trauma and stress are part of our personal experience, which we go through individually or collectively. The effects of these events may be bitter and negative, and may result a growth and a development of some psychological characteristics, which are called post in-traumatic growth. Although this development does not negate severe distress, it assumes that adversity may unintentionally lead to changes in understanding oneself, others, and the world. The current research aims to identify the level of post-traumatic growth in a sample of the physically injured people as a result of the events that Syria went through in the previous years, according to the variables of gender, age, and educational level in Damascus Governorate. The Post Traumatic Growth Scale was used by Tedeschi & Calhoun, (1996) and translated by Abdulaziz Thabet. The descriptive analytical method was used, the sample was drawn by the intentional method, as it consisted of (60) patients in Damascus governorate during the year 2021-2022. The results of the study showed the following: There is an average level of post-traumatic growth among the research sample. There are no statistically significant differences in the level of post-traumatic growth due to the variables: gender, age, and educational level.
Keywords: : Post-traumatic growth, physically injured